Polimorficzny obraz struktury rodziny w świetle współczesnej literatury psychologicznej - Walęcka-Matyja, Katarzyna (Acta Universitatis Lodziensis. Folia Psychologica, 2009)
This article reviews the literature of psychological, to show the richness and diversity of criteria, based on which scholars dealing with issues of family will attempt to define it. Given the extent of thematic work particularly focused on the presentation of the typology of families, formed on the basis of the structure of the family. The theoretical analysis of the result two main conclusions. The first relates to the fact that the systematic attempt to diverse groups of family indeed serve as cleanup discussed the phenomenon of social and allow a better understanding of the specificity of the functioning of the categories of families. In addition, allow the capture of the problems and difficulties that are associated with them. While the second proposal relates to the fact that the multiplicity and diversity found in the literature typology of families, combined with a large number of different terms used to define them is a problem for researchers involved in this issue.